Upa Adat-Based Education Management at Lumah Ajare Traditional School on Seram Island - Apriliska Titahena; Yari Dwikurnaningsih; Wasitohadi Wasitohadi (Green Publisher Indonesia, 2024)
This research aims to describe the context of the Upa Indigenous People on Manggadua and analyze the management of Upa indigenous-based education at the Indigenous School of Lumah Ajare on Seram Island. This research used realist ethnographic research. This research data was collected through observation, in-depth interviews, and documentation. Data validity testing was carried out using technical triangulation and source triangulation. The data analysis technique uses qualitative descriptive data analysis techniques with the Miles and Huberman model. The results of this research show that the Upa Indigenous People in Manggadua are the Upa people with the surname Lilihata who have lived in Saunulu for a long time. They carry out the practice of inheriting Upa traditional knowledge through the organization of the School Indigenous of Lumah Ajare. Upa indigenous-based education management at the Indigenous School of Lumah Ajare is implemented through the POAC model. This illustrates the planning of the student Siwa curriculum which combines nature and tradition as its basis in a simple manner containing nine main materials; have clear organizing by involving Care Community Local communities of Lumah Ajare as a facilitator and Indigenous Peoples as the highest decision makers; actuating, learning that runs flexibly in Indigenous Community groups; as well as controlling or supervising that is carried out well by all elements of the Indigenous Community. Upa's indigenous-based education management research can have positive implications for the sustainable inheritance of indigenous knowledge in the lives of the Seram Island Indigenous People.